2007
DOI: 10.1093/ndt/gfm618
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in serum sodium levels and other biochemical parameters among peritoneal dialysis patients

Abstract: PD patients showed seasonal variations in serum electrolyte concentration and peritoneal ultrafiltration volume. Monthly outdoor mean temperature was inversely correlated with serum electrolytes and ultrafiltration volume. A likely explanation is loss of these electrolytes through perspiration. Neglect of this annual cycle in PD patients may lead to biases in interpretation of clinical study and individual laboratory data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…We noted limited variability of serum sodium levels throughout the year, which is in contrast to recent observations in 44 Chinese peritoneal dialysis patients (5%) [6] , but in agreement with previous data evaluating seasonal variability of biochemical parameters in 1,172 HD patients in the US (0.6%, which was statistically significant but of minimal clinical relevance) [7] , possibly implicating dialysis modality and/or differences in climate as re- sponsible factors. On the other hand, predialysis sodium levels may be occasionally 'off', as indicated by the average range of 7.1 m M (as high as 16 m M in one of our subjects), demonstrating that a single measurement may not reflect the average pre-HD serum sodium.…”
Section: Discussionsupporting
confidence: 91%
“…We noted limited variability of serum sodium levels throughout the year, which is in contrast to recent observations in 44 Chinese peritoneal dialysis patients (5%) [6] , but in agreement with previous data evaluating seasonal variability of biochemical parameters in 1,172 HD patients in the US (0.6%, which was statistically significant but of minimal clinical relevance) [7] , possibly implicating dialysis modality and/or differences in climate as re- sponsible factors. On the other hand, predialysis sodium levels may be occasionally 'off', as indicated by the average range of 7.1 m M (as high as 16 m M in one of our subjects), demonstrating that a single measurement may not reflect the average pre-HD serum sodium.…”
Section: Discussionsupporting
confidence: 91%
“…The same phenomenon was also documented in PD: daily ultrafiltration volume difference of 200 mL (9). The mechanism of this variation has not been well explained; however, our previous study speculated it is related to perspiration and different patterns of PD dialysate utilization for cold and warm seasons (9).…”
mentioning
confidence: 53%
“…Peritoneal dialysis is another widely used modality of renal replacement therapy; due to its continuous nature, less abrupt changes in serum composition are presumed by most nephrologists. However, our previous study of 44 patients demonstrated that PD patients also have higher ultrafiltration volume in winter by means of more hypertonic PD solution utilization (9). The limited study subject number does not allow application of the result to all PD patients.…”
Section: Discussionmentioning
confidence: 96%
“…This is particularly of interest for this cat- ion, given the well-established seasonal variation of SNa and also the ultrafiltration volume in dialysis patient, which was shown in the paper by Li et al [11]. Given the 1-year observation period, the DR of SNa may to some extent also be subject to the influence of seasonal variation of temperature, fluid overload, interdialytic weight gain [11,[38][39][40].…”
Section: Discussionmentioning
confidence: 91%
“…However, next to an overall stability, Peixoto et al [10] also showed a variation of SNa with a yearly mean SD of SNa levels of approximately 2.0 mEq/L and a mean range of 7 mEq/L for an individual dialysis patient. Further, a seasonal variation of pre-HD SNa was shown for patients with chronic kidney disease with a range of 6.96 mEq/L from summer to winter [11].…”
Section: Introductionmentioning
confidence: 94%